2023
DOI: 10.1039/d2bm01582j
|View full text |Cite
|
Sign up to set email alerts
|

Biocide loaded shear-thinning hydrogel with anti-biofilm efficacy cures topical infection

Abstract: The Continuous intervention of multidrug-resistant (MDR) bacterial infections worsens and sluggish the dynamicity of natural wound healing processes. Fortunately, antibiotics, metal ions, or metal nanoparticle-loaded antimicrobial hydrogel were developed to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…To address this issue, researchers have successfully developed various novel and effective antimicrobial hydrogels. [281][282][283] Cai et al developed a eucalyptus essential oil nanoemulsion hydrogel specifically for this purpose. In vitro experiments demonstrated that the hydrogel displayed strong antimicrobial activity and inhibited biofilm formation.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…To address this issue, researchers have successfully developed various novel and effective antimicrobial hydrogels. [281][282][283] Cai et al developed a eucalyptus essential oil nanoemulsion hydrogel specifically for this purpose. In vitro experiments demonstrated that the hydrogel displayed strong antimicrobial activity and inhibited biofilm formation.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…4.9 Bacterial live/dead assay 42 1 mL of 10 8 CFU mL −1 midlog phase MRSA suspension in 1× PBS was mixed with the compound T, and the mixture was incubated at 37 °C. The bacterial suspension was centrifuged to extract the compound entirely after 6 h of incubation.…”
Section: Cytoplasmic Membrane Depolarization Assay 41mentioning
confidence: 99%
“…Release Kinetics of Small Antibacterial Molecule SAM-17. 44 This release kinetics of SAM-17 was measured through reverse phase (RP) HPLC. 2.5 cm diameter film was sealed in a 2 kDa cut-off dialysis membrane and then was immersed in 5 mL of different pH solutions (pH = 5.5 and pH = 7.2).…”
Section: Scanning Electron Microscopy Ofmentioning
confidence: 99%
“…Zone of Inhibition. 44 Briefly, 100 μL of 1 × 10 7 CFU/mL mid-log phases grown bacterial suspension was spread over the solid agar medium. Then, 8 mm diameter and 2 mm thick films (CHF-0 and CHF-0.1) were located at the center of the contaminated agar plate after the exclusion of a same diameter circular agar portion.…”
Section: Scanning Electron Microscopy Ofmentioning
confidence: 99%
See 1 more Smart Citation